"x^2y''+xy'-y=x^2e^x"
We will replace
"x=e^t,\\\\\nt=ln|x|,\\\\\ny'=\\frac{dy}{dx}=\\frac{y'_t}{x'_t}=\\frac{y'_t}{e^t}=e^{-t}y'_t,\\\\\ny''=\\frac{dy'}{dx}=\\frac{\\frac{dy'}{dt}}{\\frac{dx}{dt}}=\\frac{y''_te^{-t}-e^{-t}y'_t}{e^t}=e^{-2t}(y''_t-y'_t)\\\\"
Input in equation
"e^{2t}e^{-2t}(y''_t-y'_t)+e^te^{-t}y'_t-y=e^{2t}e^{e^t}"
get the equation
"y''-y=e^{2t}e^{e^t}"
Consider homogenous equation
"y''-y=0\\\\\n\\lambda^2-1=0\\implies\\lambda_1=1, \\lambda_2=-1\\\\\ny_1=e^t, y_2=e^{-t}\\\\\ny_0=c_1e^t+c_2e^{-t}"
Solution of equation find in form
"y=c_1(t)e^t+c_2(t)e^{-t}"
"c_1, c_2" find from the system
"\\left\\{\n\\begin{matrix}\n c_1'(t)e^t+c_2'(t)e^{-t}=0 \\\\\n c_1'(t)e^t-c_2'(t)e^{-t}=e^{2t}e^{e^t}\n\\end{matrix}\n\\right.\\\\\n\\left\\{\n\\begin{matrix}\n c_1'(t)=\\frac{1}{2}e^{t}e^{e^t}\\\\\n c_2'(t)=-\\frac{1}{2}e^{3t}e^{e^t}\n\\end{matrix}\n\\right.\\\\\nc_1(t)=\\int \\frac{1}{2}e^{t}e^{e^t}dt=\\frac{1}{2}e^{e^t}+k_1\\\\\nc_2(t)=-\\int \\frac{1}{2}e^{3t}e^{e^t}dt=\\\\\n=-\\frac{1}{2}(e^{2t}e^{e^t}-2e^{t}e^{e^t}+2e^{e^t})+k_2\\\\\ny=(\\frac{1}{2}e^{e^t}+k_1)e^t+\\\\\n+(-\\frac{1}{2}(e^{2t}e^{e^t}-2e^{t}e^{e^t}+2e^{e^t})+k_2)e^{-t}"
Than
"y=(\\frac{1}{2}e^x+k_1)x+(-\\frac{1}{2}(x^2e^x-2xe^x+2e^x)+k_2)x^{-1}"
Comments
Leave a comment